ANALISIS PENGGUNAAN TAGLINE PADA SETIAP USAHA PERIKLANAN MINUMAN RINGAN BERKARBONASI MEREK COCA-COLA DAN PENGARUHNYA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI KOTA SEMARANG - Rudika Harminingtyas (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2013)
The objective of this study was to analyze the effect of independent variables, namely the use of the tagline on every business advertising carbonated soft drinks of Coca-Cola brand from the aspects of density (X1), memorable (X2) and unique (X3) on the dependent variable in the form of purchase decisions ( Y) consumers in the city of Semarang. The population is the consumer brand of carbonated soft drink Coca-Cola in Semarang whose numbers can not be known with certainty. Data were obtained from 100 respondents who were sampled by means of questionnaires. To prove the hypothesis and draw conclusions, use of multiple regression analysis tool, the coefficient of determination (R2), testing the hypothesis partially with T-test and simultaneous hypothesis testing with the F-test.Based on the analysis of multiple regression known that the independent variables have a direct positive effect with the dependent variable. Further analysis of data obtained R2 value of 0.820, meaning that 82% of variation in the dependent variable is affected by the independent variable. The rest (18%) affected by other variables outside the model. Hypothesis test results either partially or simultaneously shows that the analysis results all support the hypothesis Ha1 and Ha2 proposed the use of the tagline on every business advertising carbonated soft drinks of Coca-Cola brand from the aspects of density (X1), memorable (X2) and unique (X3) have a significant effect either partially or simultaneously to the purchase decision (Y) consumers in the city of Semarang.